From the depths: Heterocaucaseuma deprofundum sp. nov., the world's deepest-occurring millipede (Diplopoda, Chordeumatida, Anthroleucosomatidae) from caves in the western Caucasus - Antić, Dragan Ž.; Turbanov, Ilya S.; Reboleira, Ana Sofia P.s. (Zootaxa, 2018)
We describe a new anthroleucosomatid millipede, Heterocaucaseuma deprofundum sp. nov., found in the second and third deepest caves of our planet, Krubera-Voronja and Sarma, in Abkhazia, western Caucasus. A brief discussion on its taxonomy and relationships within the Caucaseuma complex and genus Heterocaucaseuma is provided, together with new faunistic records on other three species of Heterocaucaseuma. Notes on the distribution and troglomorphy of the genus Heterocaucaseuma are added. Ecological information and data on the subterranean community of the Krubera-Voronja Cave are updated. We also discuss the vertical distribution of the new species in caves and the presence of an ectoparasitic fungi of the order Laboulbeniales. This new species is currently the world's deepest-occurring millipede, also representing one of the largest known chordeumatidans.